Exploration of the Implementation of Padlet Media in Increasing Involvement and Understanding of Citizens Learning Package B in Indonesian Language Subjects at PKBM Suka Maju Sejahtera Padang City - Ismaniar, Ismaniar; Arnur, Rachma Shofy (Pedagogi: Jurnal Ilmu Pendidikan, 2025)
Non-formal education has a strategic role in increasing access to learning for people who are not covered by the formal education system. One of the main challenges in Package B learning at PKBM Suka Maju Sejahtera, Padang City is the low involvement and understanding of students in the Indonesian language material. This study aims to explore the implementation of Padlet digital learning media in increasing the involvement and understanding of students. This study uses a qualitative approach with a case study method, where data is collected through in-depth interviews, participatory observation, and documentation analysis. The results of the study indicate that the use of Padlet increases the involvement of students through more active interactions, dynamic discussions, and the use of content in various formats that support conceptual understanding. However, the study also found several obstacles, such as limited internet access and lack of digital literacy. Therefore, a strategy is needed to strengthen technological infrastructure and training for tutors and students to ensure the effectiveness of using Padlet in learning. This study recommends a blended learning approach as a solution to overcome limited access and improve the learning experience of Package B residents more comprehensively